2019
DOI: 10.33259/jlivestsci.2019.53-58
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of serum Amyloid A, haptoglobin and fibrinogen levels in sheep infected with Fasciola hepatica

Abstract: The present study aimed to determine the changes in serum haptoglobin, serum amyloid A and fibrinogen levels in pathological disorders of sheep liver with Fasciola hepatica. Sixty sheep (50 with fascioliasis and 10 healthy) were used in the present study. Statistical analysis results demonstrated that SAA, Hp and fibrinogen concentration levels of the sheep infected with Fasciola hepatica were higher when compared to SAA, Hp and fibrinogen concentration levels in healthy sheep (P <0.05). While ALT, AST and GGT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Regarding the biochemical findings, in a study conducted by Denizhan et al [33] and Kılınc et al [34] on cattle with tropical theileriosis, CK-MB level was found to be significantly higher than the control group, on the other hand, by Fartashvand et al [35], CK-MB level in cattle with theileriosis was found to be quite high compared to the control group. This is considered a sign that the heart muscle of infected calves is affected.…”
Section: Resultsmentioning
confidence: 91%
“…Regarding the biochemical findings, in a study conducted by Denizhan et al [33] and Kılınc et al [34] on cattle with tropical theileriosis, CK-MB level was found to be significantly higher than the control group, on the other hand, by Fartashvand et al [35], CK-MB level in cattle with theileriosis was found to be quite high compared to the control group. This is considered a sign that the heart muscle of infected calves is affected.…”
Section: Resultsmentioning
confidence: 91%
“…Furthermore, it has been demonstrated that a methionine-rich diet was correlated with serum hyperhomocysteinemia and predisposed pigs to atherogenesis [ 52 ]. Hcy has also been investigated in cattle [ 53 , 54 , 55 , 56 ]. Its serum concentration was significantly higher than in healthy animals during bovine theileriosis [ 53 ], and in moderate, long-term cobalt deficiency [ 54 ].…”
Section: Homocysteine In Pets and Farm Animalsmentioning
confidence: 99%
“…In domestic ruminants, the most significant APPs are SAA, Hp, AGP, and Fb, whereas CRP is also an important APP in pigs. Elevated levels of these markers have been described in mastitis, lameness, and respiratory diseases in cattle (3,15), fasciolosis and scabies in sheep (17,70), and mycoplasma infection in goats (23). With regard to wildlife species, APP concentrations have been described in European bison (Bison bonasus) (52), white-tailed deer (Odocoileus virginianus) and red deer (Cervus elaphus) (13,69), bongos (Tragelaphus eurycerus) (5), Alpine ibexes (Capra ibex) (56), African buffalos (Syncerus caffer) (29), wild boars (Sus scrofa) (62), and semi-domesticated reindeers (Rangifer tarandus) (50).…”
Section: Even-toed Ungulates (Artiodactyla)mentioning
confidence: 99%